O vocabulário controlado como instrumento de organização e representação da informação na FINEP - Almeida, Tatiana de (2011)
The great volume of data and the complexity of its treatment regarding information retrieval indicate the relevance of studies on search tools. The objective of the present work is to analyse the FINEP Controlled Vocabulary (VCF) as an instrument of organization and as a representation of information originated from research proposals submitted and approved to be financed by FINEP in the fields of science, technology and innovation in the country. FINEP, concerning study areas, is described as an important system of information retrieval. The VCF analysis are based on a historical and methodological approach on the vocabulary construction, pointing out aspects of its conception and improvements over time. The work investigates the feasibility of applying classification methods for descriptors in use, aiming to contribute to the present vocabulary. Results indicate advantages of applying categorization methods on the controlled vocabulary, and emphasize the fundamental role played by the descriptor s definition as an effective element to the whole process